2016
DOI: 10.1016/j.alit.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung sounds during asthma progression in a guinea pig model

Abstract: Lung sound intensity in the middle frequency range from 501 to 1000 Hz correlated with peripheral airway wall thickness. Inspiratory sound intensity appeared to be an indicator of morphological changes in small airways in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The intensity of inspiratory lung sounds was stronger according to the progression of asthma from onset than in a control model. Furthermore, changes in lung sound intensity from 500 to 1000 Hz have been shown to be well correlated with structural changes (hyperplasia) of the bronchial wall, although these changes were limited to peripheral airways in an asthmatic animal model . A further study by Malmberg et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The intensity of inspiratory lung sounds was stronger according to the progression of asthma from onset than in a control model. Furthermore, changes in lung sound intensity from 500 to 1000 Hz have been shown to be well correlated with structural changes (hyperplasia) of the bronchial wall, although these changes were limited to peripheral airways in an asthmatic animal model . A further study by Malmberg et al .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, changes in lung sound intensity from 500 to 1000 Hz have been shown to be well correlated with structural changes (hyperplasia) of the bronchial wall, although these changes were limited to peripheral airways in an asthmatic animal model. 18 A further study by Malmberg et al reported a significant difference in the frequencies of baseline lung sounds between healthy subjects and asthmatic patients. 15 Schreur et al further reported that, at similar levels of airway obstruction, changes in both the frequency and the intensity of lung sounds with airflow were more prominent in asthma patients than in healthy subjects.…”
Section: Discussionmentioning
confidence: 93%